Cadmium chalcogenide quantum dots simulations - Wong, Rachel Xin Ci (2015)
This study aims to understand nanocrystal quantum dots (QDs) as they exhibit various interesting and unique properties that can be used for the advancement in the electrical and optical fields. We will be mainly exploring the properties of two base materials - Cadmium Sulfide (CdS) and Cadmium Selenide (CdSe) - and also Cdx(SeyS1-y) with varying “y” and “x” values, which is achieved through doping. The experiments are carried out through computer simulations to find out the structure size of the clusters and the doping effects on band gaps. The results were recorded in the form of graphs. Results showed that with an increase in number of Cadmium atoms, there is a general decrease in average band gap energies of the clusters. Also, when the clusters are doped with higher percentages of Selenium (smaller percentages of Sulfur), the band gap energies also decrease. Hence it can be seen that band gap energy varies with 1) the structure of the whole cluster and 2) the doping concentration of each element.